CURATIVE EVALUATION OF MEMALEUCA ALTERNIFOLIA OIL IN ORAL CANDIDIASIS IN IMMUNOSUPPRESSED PATIENTS - Silva, Wagner Alex de Medeiros; de Oliveira, Andréa Maria Brandão Mendes; Coelho, Luiz Fernando de Oliveira (ARACÊ, 2024)
The current research aims to verify, measure and test the microbicidal efficacy of Melaleuca essential oil in vitro against the pathogen Candida albicans. The study is experimental research, developed at MicroLAB/UFCG and BM-Biolam, evaluating the essential oil of Melaleuca alternifolia (tea tree) against pathogens in vitro in Saboraud dextrose agar - ASD, subjecting them to variation factors, incubated in a BOD type incubator at 36±1°C, according to the quantitative inoculum of the microorganism. For the Candida albicans, the MIC (Minimum Inhibitory Concentration) of 16 μL g-1 (EC50%) in CA-I to up to 128 mL×g-1 (EC100%) in CA-II of the isolated TTO demonstrated activity equivalent to Cet, reaching its maximum efficacy at the EC100% of 240 mL×g-1 in CA-III when associated. Regarding the remissive effect (ERD), the probability of survival - PS in 50% (IC50) in CA-I was 19.1% (A), in CA-II with the index of 35.7% (C) and in CA-III at the value close to 44.4% (E). In this context, when evaluating the antibiograms against the taxa, it is possible to suggest the use of TTO in the preparation of mouthwashes with a value of [sca]£128 mL×g-1 and D³16 mm, attesting to the viability of including the essential oil as a phytotherapeutic agent as a complementary alternative route in clinical dental treatments caused by Candida albicans that trigger oral candidiasis, being effective against the pathogen described, eliminating it in a time interval of T£8 days when associated.